Reading the Song of songs with St. Thomas Aquinas - Bonino, Serge-Thomas (Thomistic ressourcement series, 2023)
"St. Thomas Aquinas never commented on the Song of Songs. The purpose of this book is to demonstrate, however, that he meditated on it and absorbed it, so that the words of the Song are for him a familiar repertoire and a theological source. His work contains numerous citations of the Song, not counting his borrowings of vocabulary and images from it. In total, there are 312 citations of the Song in Aquinas's corpus, along with citations of the Song that are found in citations that Aquinas makes of other authors (as for example in the Catena aurea). Understanding the purpose and placement of these citations significantly enriches our understanding of Aquinas as a theologian, biblical exegete, and spiritual master. The book contains an Appendix listing and contextualizing each citation. The study of the citations of the Song especially illuminates Aquinas's spiritual doctrine. By citing the Song, Aquinas emphasizes the spiritual life's path of dynamic ascent, through an ever increasing participation in the mystery of the nuptial union of Christ and the Church through love. The Song also highlights the eschatological tension or yearning present in the spiritual life, which is ordered to the fullness of beatific vision. Although Aquinas's theology is highly "intellectual," by citing the Song he brings out the affective character of the spiritual life and conveys the centrality of love in the soul's journey toward Christ. He also draws together contemplation and preaching through his use of the Song"--